Male deity statue to the right of the Mukhamandapa - Temples of India Project Team (Jio Institute, 2024)
To the right of the mukhamandapa (front porch), of the Mahakal Temple, entrance stands another male deity statue. This deity, depicted in a standing posture, has several arms, now damaged. Adorned with a jatamukuta (a crown of matted hair) and sporting a beard, he is accompanied by an attendant depicted at the base, while gandharvas (celestial beings) are carved at the top corners.